Impact of Ultraviolet Radiation on Skin and Blood Melanin Traits in Xichou Black-Boned Chicken: A Transcriptomic and Metabolomic Study - Xinlu Li; Zhongxiao Tian; Haojie Li; Lei Tan; Yong Zhang; Changrong Ge; Kun Wang (Animals)
This study investigated the effects of ultraviolet A (UVA) radiation on the blackness traits of Xichou Black-boned Chickens and their underlying molecular mechanisms through combined transcriptomic and metabolomic analyses. A total of 240 one-day-old Xichou Black-boned Chickens were randomly divided into four groups and exposed to different durations of UVA radiation at an intensity of 47 μW/cm2. Skin blackness was measured at 1, 22, and 45 days of age, and blood and pectoral skin samples were collected at 45 days for analysis. The results showed that an exposure time of 1 h per day at 47 μW/cm2 was ideal for enhancing the blackness traits of the chickens, while exposure times exceeding 3 h led to a significant increase in mortality. Omics studies revealed that the mTOR pathway and tryptophan metabolism pathway are potentially involved in the biological processes by which UVA radiation affects the blackness traits of Xichou Black-boned Chickens, with the FZD3 gene being a candidate gene for these effects. These findings provide theoretical foundations and references for understanding the molecular regulation of blackness traits in these chickens and the potential application of UVA radiation in their production.